(untitled) (Journal of Universal Science Research, 2025)
This article is dedicated to the section of lexicology concerning phraseology. It presents a comparative linguacultural analysis of phraseological and idiomatic units involving clothing names in English and Uzbek. Additionally, the specific features of phraseological expressions that vividly reflect the mentality, culture, customs, and traditions of each nation are revealed from the perspective of both languages (English and Uzbek). The article also provides important information about phraseological units.